A SYSTEM OF ANALYSIS OF THE TOTAL LIABILITIES TO TOTAL ASSETS RATIO - Subačienė, Rasa; Villis, Liuda (Ekonomika, 2010)
The problem of solvency, which has been dealt with in many authors’ works, is exceptionally topical nowadays when settlements among companies are performed not in a timely manner, disturbing business possibilities to remain active in the times of economic recession. Solvency represents a company’s ability to cover current and non-current liabilities; also, it influences a company’s financial state, results of activities and further development. Therefore, analysis of solvency provides the basis for evaluating a company’s financial state.The means of assessing the total liabilities to total assets ratio by applying a system of pyramidal analysis, which reveals the actions that have a negative impact on this ratio, were investigated for the first time. The total liabilities to total assets ratio was selected as one of the long-term solvency ratios representing a company’s total level of liabilities and its further capacity of borrowing.The purpose of the article is to present a system of analysis of the total liabilities to total assets ratio. The methods used for this purpose were analysis of academic materials, filing of information, comparison and summarizing.